Optimation of NaOH Catalyst Consentration on 1,3-Diphenyl-2-propen-1-on Synthesis Using Microwave-Assisted Organic Synthesis (MAOS) Method - Iin Narwanti; Narendra Bagus Kusumajati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
with a variation of NaOH catalyst concentration has been done. The purpose of this study was to determine the concentration of NaOH catalyst in the synthesis of 1,3-diphenyl-2-propen-1-on using MAOS method which produced optimal yield. The synthesis of 1,3-diphenyl-2-propen-1-on using benzaldehyde and acetophenone was carried out using the MAOS method with NaOH catalyst. The variation of NaOH catalyst concentration was 10%, 20%, 30%, and 40%. Microwave radiation was carried out at 140 watts for 20 seconds. The purity of the synthesized 1,3-diphenyl-2-propen-1-on was tested by melting point, TLC, and gas chromatography. The structure of the synthesized 1,3-diphenyl-2-propen-1-on was characterized by FTIR, GC-MS and NMR. The results showed that the compound 1,3-diphenyl-2-propen-1-on can be synthesized from benzaldehyde and acetophenone using MAOS method. The obtained yield at varying catalyst concentrations of 10, 20, 30 and 40% were (50.58±1.84%, (69.20±1.58)%, (84.55±1.50)% and (90.60±0.96)%, respectively. The concentration of 40% NaOH catalyst produces the most optimal yield of synthesis products.